Neurospora crassa chromosome walks - M A Nelson; D O NATVIG (Fungal Genetics Reports, 1998)
Chromosome walks have been executed for all seven chromosomes of N. crassa, but the amount of coverage varies greatly, from less than 3% (LG V) to about 25% (LG VII). Overall, about 10% of the genome has been covered by chromosome walks (Table 1). All chromosome walks are shown with respect to the position on the chromosome, oriented from the left telomere to the right. The standard nomenclature for these genomic libraries is followed: pSV50 (Vollmer and Yanofsky 1986 Proc. Natl. Acad. Sci. USA 83:4869-4873), pMOcosX (Orbach 1994 Gene 150:159-162), EMBL3 (Yeadon and Catcheside 1995 Curr. Genet. 28:155-163), pCRD103 (Davis et al. 1994 Genetics 136:1297-1306), CBM1 (Cabibbo et al. 1991 Fungal Genet. Newsl. 38:68-70), CBM2 (Ballario et al. 1996 EMBO J. 15:1650-1657) and yeast artificial chromosome (YAC; Centola et al. 1994 Fungal Genet. Newsl. 41:23-33). For precise map positions of the cited alleles, refer to Perkins et al.(1982 Microbiol. Rev. 46:426-570) and Perkins (1992 Fungal Genet. Newsl. 39:61-70).